2021
DOI: 10.1149/2162-8777/ac0500
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Downstream Plasma Exposure on β-Ga2O3 Rectifiers

Abstract: The effects of downstream plasma exposure with O2, N2 or CF4 discharges on Si-doped Ga2O3 Schottky diode forward and reverse current-voltage characteristics were investigated. The samples were exposed to discharges with rf power of 50 W plasma at a pressure of 400 mTorr and a fixed treatment time of 1 min to simulate dielectric layer removal, photoresist ashing or surface cleaning steps. Schottky contacts were deposited through a shadow mask after exposure to avoid any changes to the surface. A Schottky barrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…On the other hand, significant surface degradation was found after plasma exposure, and the damage did not recover fully even after annealing at 500 °C. Xia et al . investigated the effects of downstream plasma exposure with O 2 , N 2 , and CF 4 discharges on Si-doped β-Ga 2 O 3 Schottky barrier diodes fabricated on HVPE-grown 10 μm thick β-Ga 2 O 3 to separate chemical effects from physical damage due to ion bombardment and to simulate processes like photoresist ashing, dielectric removal, and surface cleaning that occur during device fabrication.…”
Section: Schottky Contacts To Ga2o3mentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, significant surface degradation was found after plasma exposure, and the damage did not recover fully even after annealing at 500 °C. Xia et al . investigated the effects of downstream plasma exposure with O 2 , N 2 , and CF 4 discharges on Si-doped β-Ga 2 O 3 Schottky barrier diodes fabricated on HVPE-grown 10 μm thick β-Ga 2 O 3 to separate chemical effects from physical damage due to ion bombardment and to simulate processes like photoresist ashing, dielectric removal, and surface cleaning that occur during device fabrication.…”
Section: Schottky Contacts To Ga2o3mentioning
confidence: 99%
“…191 On the other hand, significant surface degradation was found after plasma exposure, and the damage did not recover fully even after annealing at 500 °C. Xia et al 192 194 They observed a near-ideal reverse leakage current attributed to the TFE tunnelling mechanism in surface electric field in the range from 0.8 MV/cm to 3.4 MV/cm. The SBHs in the range 1.37−1.40 eV extracted from reverse I−V characteristics were consistent with values extracted from forward I−V and C−V characteristics.…”
Section: Schottky Contacts To Ga 2 Omentioning
confidence: 99%
See 1 more Smart Citation